Understanding plant-beneficial microbe interactions for sustainable agriculture - A R Podile, S Ankati, (Journal of Spices and Aromatic Crops, 2019)
A better understanding of the specific molecular interactions between plants and microbes is crucial to develop newer strategies for sustainable agriculture. The productivity of wide range of agricultural crops under decreasing land resources and shrinking biological potential of the soil need to be improved. Search for useful microorganisms associated with the plants has been highly productive for sustainable agriculture. We take a close look at the current level of molecular interactions that mostly involve specific molecular patterns of microbes and their cognate receptors in plants and development of efficient biofertilizers for improving crop yields. This article covers the broader aspects of plant-microbe interactions with more focus on plant growth promoting rhizobacteria (PGPR). Further upcoming strategies to understand the plant-PGPR interactions are discussed.